Derrida and Husserl : the basic problem of phenomenology - Lawlor, Leonard, 1954- (Studies in Continental thought., 2002)
Lawlor illuminates Husserl's influence on the French philosophical tradition that inspired Derrida's thought. Beginning with Eugen Fink's pivotal essay on Husserl's philosophy, he carefully reconstructs the conceptual context in which Derrida developed his interpretation of Husserl.